EFFECT OF A PARTICIPATORY ENVIRONMENTAL EDUCATION PROGRAMME ON TRADERS’ KNOWLEDGE, ATTITUDES AND PRACTICES IN SOLID WASTE MANAGEMENT IN OYO STATE, NIGERIA (2014)
The problem associated with solid waste management in Oyo State, Nigeria has been traced by researchers to poor environmental awareness and low level of education among the populace, especially traders, who generated much of the waste. These traders however have been excluded from various environmental awareness education programme. This study, therefore, examined the effect of a participatory environmental education programme on traders’ knowledge, attitudes and practices in solid waste management in some selected markets in Oyo State, Nigeria. The study adopted a pretest-posttest, control group, quasi-experimental design with a 2x2x2 factorial matrix. The sample consisted of 1000 traders (560 female and 440 male) from twenty markets in Oyo State using the stratified random sampling technique. Three main instruments were used to collect data, namely, Environmental Knowledge Test (r=083), Environmental Attitude Scale and (r=0.85), Environmental Practices Scale (r=075). These instruments were translated into Yoruba language because majority of the participants had little or no formal education. Participants in the experimental group were exposed to a participatory environment method, while those in the control group were exposed to the placebo method. The treatment lasted for a period of twelve weeks. Seven hypotheses were tested at 0.05 level of significance. Data were analysed using descriptive statistics and Analysis of Covariance (ANCOVA). It was found that treatment had significant main effect on traders’ knowledge (F (1,480), =22.55; p < .05), attitudes, (F (1,480) = 75. 18; p <0.05) and practices (F(1,481) = 48:78; p <0.05) in solid waste management. Traders exposed to participatory environmental education programme performed better in knowledge (=47.83) than their control group counterparts (=46.83). Similarly, participants in the participatory group had a better attitude score ( = 42.88) than the control group ( = 33.64), and the same pattern was observed in the practice scores with those in experimental group having higher practices score (= 40.98) than control group (= 32.97) in solid waste management. It was also found that location of traders had significant effect on their knowledge, attitudes and practices. Traders from the urban areas obtained a higher knowledge score than their rural counterparts ( = 38.29) and a higher practices mean score ( = 41.32) than their rural counterparts ( = 35.29). Gender was found to have no significant main effect on traders’ knowledge, attitudes and practices in solid waste management. Participatory environmental education programme was effective in improving traders’ knowledge, attitudes and practices in solid waste management. It is therefore recommended that participatory environmental education programme be adopted by all waste management agencies for enlightening traders on solid waste management and by all the agencies of government in charge of solid waste management in Nigeria